Design and enhanced gene silencing activity of spherical 2′-fluoroarabinose nucleic acids (FANA-SNAs). Issue 8 (15th January 2021) - Fakih, Hassan H.; Katolik, Adam; Malek-Adamian, Elise; Fakhoury, Johans J.; Kaviani, Sepideh; Damha, Masad J.; Sleiman, Hanadi F.
Abstract : Optimizing FANA modified spherical nucleic acids (FANA-SNAs) for highly efficient delivery of nucleic acid therapeutics. Abstract : Drug delivery vectors for nucleic acid therapeutics (NATs) face significant barriers for translation into the clinic. Spherical nucleic acids (SNAs) – nanoparticles with an exterior shell made up of DNA strands and a hydrophobic interior – have recently shown great potential as vehicles to improve the biodistribution and efficacy of NATs. To date, SNA design has not taken advantage of the powerful chemical modifications available to NATs. Here, we modify SNAs with 2′-deoxy-2′-fluoro-d -arabinonucleic acid (FANA-SNA), and show increased stability, enhanced gene silencing potency and unaided uptake (gymnosis) as compared to free FANA. By varying the spacer region between the nucleic acid strand and the attached hydrophobic polymer, we show that a cleavable DNA based spacer is essential for maximum activity. This design feature will be important when implementing functionalized nucleic acids into nanostructures for gene silencing. The modularity of the FANA-SNA was demonstrated by silencing two different targets. Transfection-free delivery was superior for the modified SNA compared to the free FANA oligonucleotide.